Use of diuretics as doping agents in sport - Antić Dušan (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Diuretics are drugs used to treat hypertension, acute and chronic edema, cardiac and renal failure and other conditions. In addition to their use as drugs, diuretics are often abused in sports as doping agents. On the list of prohibited substances in sport diuretics can be found for more than 25 years. There are two possible reasons for their use as doping: to reduce in the short term weight of athletes in sports with weight categories, or to accelerate the excretion in urine of other doping substances (mostly anabolic steroids). According to the World Anti-Doping Agency, in the past ten years diuretics were present in 5-8% of all doping positive cases. Almost the same situation is in Serbia. What is more, in Serbia in 2010 even 22.6% of all punished athletes used diuretics. Considering the effects of diuretics on human body, it is necessary to be very cautious with their use (abuse) due to the fact that consequences could be fatal.